Gayo Islamic Education Architects and Contributions to Gayo Islamic Education Treasures in the Era of 1900-1986 - Zulkarnain, Zulkarnain; Harun, Ihsan; Yusdiana, Emy (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The emergence and development of Islamic intellectual civilization in the Era of 1900-1986 started from from the scientific research process or further studies of the Gayo Islamic education figures in the Era of 1900-1986 at well-known educational centers at that time such as: Pulo Kitun, Cet Merak and Samalanga, Thawalib West Sumatra and Bangil East Java. The ideas of these figures are as follows: Tgk. Abdul Kadir (Tgk. Pasir) (1910) Tgk Abdurrahman Daudi/Tgk. Mude Kala (1911-1962) Tgk. H. Abdurrahman Bebesen (1911-1995) Tgk. Ahmad Damanhuri/Tgk. Cross.(1915-1940) Tgk. Abdul Djalil (1915-1974) Tgk. H. Mohd. Ali Djadun (1927-2016) Mr. H. Mohd. Ali Djadun (1927-2016) Mr. M. Hasan Tan (1949-2016) was more or less influenced by the 4 networks that existed in Gayo, namely: Gayo-Gayo, Gayo-Bireuan, Gayo-Thawalib and Gayo-Bangil, in addition to his role as an influential scholar in Gayo. Based on their educational network and character as an ulama or Tgk, they played an important role in initiating the establishment of formal and non-formal educational institutions that became the forerunner and transformed into Islamic educational institutions in Gayo at the end of the 1900s Era.